INSTRUMENTAL ERRORS OF TRANSMISSION LINE PARAMETERS METER - Shcherbyna, Olga; Zaliskyi, Maksym; Petrova, Yuliia; Kozhokhina, Olena (Science-based technologies, 2022)
The article is devoted to the construction of the instrumental errors dependences of the transmission line parameters meter on the parameters of the physical or structural hardware components of the meter. For this, when constructing a mathematical model, only the main functional connections between the structural links of the measuring device were selected, neglecting the influence of external factors on the stability of the structural elements parameters. As is know, each measuring instrument must have a certain set of metrological characteristics. According to these characteristics, measuring instruments are selected for use in certain technological processes, and it is they that determine the reliability of the data obtained as a result of measurements. These characteristics include a list of physical quantities that can be measured, the conditions under which the measurement process can be carried out, metrological (informational) reliability, accuracy class or permissible errors of the measuring instrument itself. The conditions under which the measuring instruments can be used depend on the constructive and technological implementation of the device, since the measurement technique and its implementation in the electrical circuit are not accompanied by special requirements for the operation of the device. This means that such a meter can be produced with a focus on laboratory use, for use in a mobile version and in the field, for use in complex electronic systems as an element of built-in control, etc. All this follows from the given measurement technique and analysis of the synthesized meter circuit. The exact characteristics of a measuring instrument include two important components: method errors and instrumental errors. To build such dependencies on the parameters of physical or structural hardware components and the values of the measured quantities, it is necessary to build a mathematical model of the measuring equipment. It is advisable to restrict ourselves to the construction of a mathematical model, which will take into account the dominant factors of the accuracy characteristics that cause first-order errors. Such a model, depending on the needs that arise during the operation of the measuring instrument, can be supplemented by certain sources of influences, certain causal actions that will cause the appearance of errors of the second and even third order. These are errors caused by changes in temperature, humidity, atmospheric pressure, mechanical vibrations, electromagnetic and acoustic fields, etc.